Etika Pola Komunikasi Dalam Al-Qur'an - Nurul Abrari (Prisani Cendekia Institute, 2023)
In essence, communication is a need for every human being as a social entity, so communication is a technique of interacting with others. There are certain ethical principles in communication that must be followed when speaking with other individuals. Islam also teaches communication ethics contained in the Qur'an and the sunnah of the Prophet. Since every person and every community has values ??that they adhere to, discussing human communication also involves discussing the values ??or ethics that those individuals or cultures uphold. The importance of internal morality because culture and communication are interdependent, so communication seeks to improve our ability to communicate (become communicative). The two interact. What we see, notice, or ignore, what we talk about, how we earn, how we invest, and how we influence are all influenced by culture. then, different. The findings of this study also show that the Qur'an contains verses that explain the ethics of communication. The word